Preparation and characterization of uniform, spherical particles of Y2O2S and Y2O2S:Eu - Delgado Da Vila, Ligia [UNESP]; Stucchi, Elizabeth Berwerth [UNESP]; Davolos, Marian Rosaly [UNESP] (Royal Society of Chemistry (RSC), 1997)
The preparation of spherical Y2O2S and Y2O2S:Eu particles using a solid-gas reaction of monodispersed precursors with elemental sulfur vapor under an argon atmosphere has been investigated. The precursors, undoped and doped yttrium basic carbonates, are synthesized by aging a stock solution containing the respective cation chloride and urea at 82-84 °C. Y2O2S and Y2O2S:Eu were characterized in terms of their composition, crystallinity and morphology by chemical analysis, X-ray powder diffraction (XRD), IR spectroscopy, and scanning electron microscopy (SEM). The Eu-doped oxysulfide was also characterized by atomic absorption spectrophotometry and luminescence spectroscopy. The spherical morphology of oxysulfide products and of basic carbonate precursors suggests a topotatic inter-relationship between both compounds.